Digital transformation of public-private partnership tools - Lyudmila Tolstolesova; Igor Glukhikh; Natalya Yumanova; Otabek Arzikulov (Journal of Risk and Financial Management, 2021)
The need for modern infrastructure as a prerequisite for sustainable development, poverty alleviation, and improvement of the quality of life of the population is a global problem that requires searching for and attracting large amounts of long-term investments. The presence of this problem in recent decades has led to the increasing implementation of complex and costly infrastructure projects through the public-private partnership (PPP) mechanism with high potential for attracting investment. This mechanism, in conditions of limited financial opportunities, allows one to combine the financial resources of the public and private parties for the implementation of major infrastructure projects. The limited use of existing tools at different stages of PPP projects and the increasing need for additional resources make it necessary to consider the possibility of using digital tools that complement traditional ones. For this purpose, the authors analyze existing financing tools, revealing their advantages and disadvantages, and identify and justify the possibility of using digital tools in the implementation of PPP projects. However, digitalization includes not only financing tools but also the development of infrastructure, including digital platforms needed to conduct such operations in the digital environment. As a result, a combined financing toolkit can be formed for each phase of project realization, including traditional and digital tools. The results of this study will become a basis for revealing the directions of the digital transformation of the PPP mechanism.
Keywords: 330; digital financial instruments; digital investments; digital transformation; project financing tools; public-private partnership mechanism; specialized and integrated digital platforms